METHODOLOGY OF CONTEMPORARY ISLAMIC THOUGHT - Ningsih, Titik (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
The study of the currently developing mode of thought of Islam (Mode of Thought), which is then known as contemporary Islamic thought, through an investigation of the logic and reasoning that has a role behind this thought. With regard to attitudes toward the emergence of modernism, liberalism, traditionalism, fundamentalism, cultural Islam, and structural Islam in general, the main problems of contemporary Islamic thought. The method used in this research is literature study, which tries to reveal by analyzing textually and contextually. Textual analysis is carried out using several interpretations and relevant journals, while contextual analysis is the author's understanding so as to form a complete understanding The results of the discussion can be described as follows The growth of contemporary modes of Islamic thought in order to straighten out the real meaning related to the existence of terms because these trends and modes of thought cannot escape from the dynamics of thought in the last four to five decades. We can see the defeat of science and technology, even the defeat of civilization during the defeat of Arab Islamic politics in 1967. Concern for cultural heritage, traditions, or turrets has created a new awareness so that it can be transformed into the present so that it remains current and can solve contemporary problems. Likewise, science and technology born of modernity are sought to be utilized for progress and solving contemporary problems. So the mode of contemporary Islamic thought generally makes epistemology, reason, 'aqal, book or paradigm as the basis for the growth and development of science and tradition as the object of their thought. This shows that tradition and modernity are historical, not natural